Integrating GIS in Classroom Practice: Empirical Evidence on What Drives Teachers to Use Geospatial Technology (Architecture Image Studies, 2025)
The integration of geospatial technologies such as GIS, remote sensing, and GPS has become increasingly important for advancing spatial thinking skills and geographic literacy in secondary education. However, empirical evidence on the psychological and pedagogical factors that shape teachers’ adoption of geospatial technologies—particularly in developing countries—remains limited. This study examines how geospatial awareness and geospatial knowledge shape the actual implementation of geospatial technologies among secondary school geography teachers in Indonesia. Drawing on survey data from 110 teachers across diverse regions and using a Structural Equation Modeling (SEM) approach, the study highlights that teachers’ geospatial awareness and knowledge significantly influence the actual implementation of geospatial technologies in classroom-based geography instruction. Nevertheless, the findings indicate that awareness alone is insufficient to translate into classroom action unless accompanied by adequate technical competence. Generational differences further accentuate the digital proficiency gap, with younger teachers demonstrating stronger operational skills. These findings advance theoretical understanding of the awareness–knowledge–practice mechanism and provide practical guidance for geospatial education reform. The study underlines an urgent need for hands-on GIS training, differentiated professional development, and institutional support to strengthen geospatial literacy in Indonesian schools and in other developing-country contexts.